The impact of social transfers on inequality measured by GINI index: The example of Macedonia - Saso Kozuharov; Vladimir Petkovski (UTMS Journal of Economics, 2018)
Through the past few decades the problem of income inequality and welfare segregation has become quite significant for the economies of the countries worldwide. Republic of Macedonia as a country in development is presented with a serious challenge into decreasing the income inequality witch has risen for average 4% annually over the past 15 years, according to the GINI index. Socio-economic inequality can be represented as major problem for a developing country, and must be considered as one of main priorities for increasing the economic development in the following years. Many factors can be targeted as to influence the socio-economic segregation, one of them being the social protection program. The main goal of this article is to show the impact of social transfer expenditures on the socio economic inequality in Republic of Macedonia measured through the GINI index. In accordance to reaching this goal, the econometric model of regression and correlation was conducted towards determination of the linkage between the social transfers and inequality measured with Gini coefficient. According to the conducted research a true bond and thus the impact on inequality by the social transfer expenditures was determined.
Keywords: G17; C22; G32; 330; income segregation; welfare; social protection benefits; social expenditures